The Challenge of Coordination in Management of Coronavirus Disease 2019 (covid-19) in Surabaya - Choiriyah Basnawi (Airlangga Development Journal, 2021)
Coordination is one of the important aspects in the management of Covid-19 handling in Surabaya. In itsimplementation, some problems arise such as the problem of ego-sectoral that becomes one of the obstacles inhandling this coordination process. Problems related to coordination also appear in various mass media, this factshows that the problem of coordination related to Covid-19 handling in Surabaya is a strategic and interestingissue to study. The writing method used in this paper is a literature review to find the formulation of appropriateand effective forms of coordination patterns. The writer also collected Primary data from online discussions todescribe the pattern of coordination from the other Local Government Agencies as a form of best practice thatmight be adopted in Surabaya so that they could build better management of Covid-19 handling in Surabaya.The results showed that the pattern of coordination in the management of Covid-19 handling that is initiated bythe Surabaya City Government needs some improvement. In vertical coordination, it is necessary to strengthengood coordination between the City Government of Surabaya and the Government of the Province of East Java.For Horizontal coordination, Surabaya Government needs to reinforce the coordination with the city or districtgovernment in the surrounding area. These things are necessary because Surabaya is an agglomeration areawhere there are still many people who do mobility in and out. The conclusion from this study is that there is aneed to strengthen coordination patterns both vertically and horizontally with various stakeholders involved inthe management of Covid-19 handling in Surabaya. At the end of this paper, the researcher also gave arecommendation and trying to show best practices in applying the coordination pattern that has been carried outby other regional governments as a form of illustration that might be able to be adopted to improve Covid-19handling in Surabaya.